2006
DOI: 10.1590/s0102-86502006000700008
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative effect of the aqueous extract of Hyptis pectinata on liver regeneration after partial hepatectomy in rats

Abstract: Proliferative effect of the aqueous extract of Hyptis pectinata on liver regeneration after partial hepatectomy in rats 8 -ORIGINAL ARTICLE Proliferative effect of the aqueous extract of Hyptis pectinata on liver regeneration after partial hepatectomy in rats 1 Efeito do extrato aquoso da Hyptis pectinata na regeneração hepática após hepatectomia parcial em ratos ABSTRACT Purpose: This study was carried out to assess the effects of the aqueous extract of Hyptis pectinata leaves on liver regeneration and on se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…have been shown to have anti-inflammatory (Grassi et al, 2006) and antiplasmodial properties (Chukwujekwu et al, 2005). Essential oils isolated from the genus Hyptis, have also been shown to have analgesic and regenerative properties (Melo et al, 2006;Santos et al, 2007;Menezes et al, 2007;Arrigoni-Blank et al, 2008). According to the wide range of activity of the genus, related to skin diseases, and the lack of references on Hyptis lacustris specifically, this plant should be considered for activity-guided fractionation studies.…”
Section: Leishmaniasismentioning
confidence: 99%
“…have been shown to have anti-inflammatory (Grassi et al, 2006) and antiplasmodial properties (Chukwujekwu et al, 2005). Essential oils isolated from the genus Hyptis, have also been shown to have analgesic and regenerative properties (Melo et al, 2006;Santos et al, 2007;Menezes et al, 2007;Arrigoni-Blank et al, 2008). According to the wide range of activity of the genus, related to skin diseases, and the lack of references on Hyptis lacustris specifically, this plant should be considered for activity-guided fractionation studies.…”
Section: Leishmaniasismentioning
confidence: 99%
“…Statistical comparisons among the groups were performed by analysis of variance for parametric measurements with Bonferroni as posttest. (5). In that study we were able to test different concentrations of aqueous extracts of the plant, obtaining an optimal effect on hepatocyte proliferation at 100 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies, it has been shown that an aqueous extract of Hyptis pectinata leaves protects the liver against injuries, stimulates its regeneration according to concentration, and has antinociceptive and antiedematogenic effects (3)(4)(5). Although the mechanism of biostimulation or inhibition remains obscure, some recent studies indicate that mitochondria may be the target organelle of the plants (6,7).…”
mentioning
confidence: 99%
“…The phytochemical content of Hyptis pectinata generally has a skeleton of α, β-unsaturated lactones, such as hyptolide compounds (Achmad et al, 1987), pectinolides A-C, sambacaitaric acid, rosmarinic acid (Falcao et al, 2013), pectinolides D-G (Boalino et al, 2003), and spicigerolide (Almtorp et al, 1991). The discovery of α, β-unsaturated lactones is an interesting study because of its potential effect as antinociceptive, antiedematogenic (Franzotti et al, 2001), antileishmanial (Falcao et al, 2013), antimalarial (Melo et al, 2006), antibacterial (Santos et al, 2008), and anticancer (Asy and Suzery, 2019;. The previous study reported that hyptolide has a basic framework of α, β-unsaturated C12-δ-lactones with a chemical formula, C 18 H 24 O 8 (Achmad et al, 1987).…”
Section: Introductionmentioning
confidence: 99%